The role of community pharmacists in medicines optimisation for housebound people: A scoping review - Jennifer Blease; Yahvi Bhonsle; Rose Ireson; Albert Farroha; Greg Westley; Richard Cooper; Daniel Hind (PLoS ONE, 2025)
Background An increasingly ageing population presents many challenges for healthcare systems, including how to support older adults who are more likely to be both housebound and have complex medication needs. Community pharmacists may play a key role in medicines optimisation for this vulnerable population, however, the extent of literature exploring this topic is unclear. Objective To map existing literature on the role of community pharmacists in medicines optimisation for housebound older adults in the United Kingdom (UK). Methods A scoping review was conducted following PRISMA-ScR guidelines. Peer-reviewed primary research and grey literature published since 2000 were searched using relevant databases and websites. Data was charted using a standardised form based on TIDieR guidelines and EPOC taxonomies. A narrative synthesis was conducted to summarise and interpret the findings from included studies. Results Seven sources were included in the review – five peer-reviewed articles and two grey literature reports. Interventions consisted of domiciliary medication reviews conducted by pharmacists. Key medicines optimisation strategies addressed were medication review, deprescribing, addressing polypharmacy and facilitating communication between providers. Reported outcomes included identification of widespread issues with polypharmacy and medication-related problems, reduced hospital admissions, cost savings and improved patient care. Gaps identified were limited generalisability, lack of comparisons to standard care, and under-representation of minority groups. Conclusions The literature indicates promise for the role of community pharmacists in medicines optimisation for housebound older adults through domiciliary services. However, more research is needed to evaluate the effectiveness and feasibility of pharmacist-led interventions in this setting. Addressing identified gaps will help inform pharmacists’ roles in supporting medication needs of housebound patients.